2009
DOI: 10.1534/genetics.109.105775
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Sex-Dependent Gene Expression in Three Recently Diverged Species of Drosophila

Abstract: Sexual dimorphism in morphological, physiological, and behavioral traits is pervasive in animals, as is the observation of strong sexual dimorphism in genomewide patterns of gene expression in the few species where this has been studied. Studies of transcriptome divergence show that most interspecific transcriptional divergence is highly sex dependent, an observation consistent with the action of sexdependent natural selection during species divergence. However, few transcriptome evolution studies have been co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
67
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 69 publications
(97 reference statements)
18
67
1
Order By: Relevance
“…These results are similar to those observed in D. pulex , where 25% of the genes are classified as sex-biased with a P value cut-off of 0.05, and 10% are classified as sex-biased with a fold-change cut-off of 2 (supplementary table S4, Supplementary Material online). The proportion of sex-biased genes is much less than that reported for Drosophila species where as many as two-thirds of all genes can show sex-biased expression when whole animals are assayed (Gnad and Parsch 2006; Jiang and Machado 2009; Meisel et al 2012). However, in D. melanogaster , the proportion of genes showing sex-biased expression can vary greatly among tissues (Huylmans and Parsch 2015).…”
Section: Discussionmentioning
confidence: 64%
“…These results are similar to those observed in D. pulex , where 25% of the genes are classified as sex-biased with a P value cut-off of 0.05, and 10% are classified as sex-biased with a fold-change cut-off of 2 (supplementary table S4, Supplementary Material online). The proportion of sex-biased genes is much less than that reported for Drosophila species where as many as two-thirds of all genes can show sex-biased expression when whole animals are assayed (Gnad and Parsch 2006; Jiang and Machado 2009; Meisel et al 2012). However, in D. melanogaster , the proportion of genes showing sex-biased expression can vary greatly among tissues (Huylmans and Parsch 2015).…”
Section: Discussionmentioning
confidence: 64%
“…Instead, we found that male-biased genes tend to have higher expression divergence in females, and female-biased genes have higher expression divergence in males. This suggests that sex-biased genes experience high selective pressure in the opposite sex (Jiang and Machado 2009). …”
Section: Better Conservation Of Male-biased Gene Expression On the Nementioning
confidence: 99%
“…In line with this, studies in a wide array of organisms have attempted to determine the differences in gene expression between males and females (Parsch and Ellegren 2013), including Drosophila (Assis et al 2012; Perry et al 2014), birds (Pointer et al 2013), nematodes (Albritton et al 2014), and brown alga (Lipinska et al 2015). These works have revealed that a significant fraction of genes in the genome exhibit differential expression between males and females (Rinn and Snyder 2005; Mank, Hultin-Rosenberg, Webster, et al 2008; Reinius et al 2008; Jiang and Machado 2009), which suggests that the expression of sexual dimorphism is related to marked genetic reprogramming (Lipinska et al 2015). …”
Section: Introductionmentioning
confidence: 99%